Analisis Proses Seleksi Terhadap Kinerja Pekerja Migran Indonesia Dengan Penempatan Kerja Sebagai Variabel Intervening (Studi Kasus Dinas Ketenagakerjaan Kota Medan) - Penny Chariti Lumbanraja (SMART Management Journal, 2021)
Important assets that must be considered in the implementation of national development are SDA (natural resources) and HR (human resources). In general, the success of a company or organization depends on the people involved in it, so a strategy is needed to achieve this. This research is intended to determine the effect of the selection process on the performance of Indonesian Migrant Workers (PMI) with work placement as an intermediary variable. The data collection techniques are surveys, interviews, and questionnaires. While the research method used is simple random sampling method. This study has 100 PMI respondents, and analyzed using SEM analysis. The results of this study are the positive and significant influence of the selection process on the performance of migrant workers through job placement as an intervening variable